Impact of Problem-Based Learning on Adversity Quotient with Self-Efficacy as a Moderator in Seventh-Grade Science Education - Zulhikmah Permatasari; Riezky Maya Probosari; Bayu Antrakusuma (PAEDAGOGIA, 2024)
This study aims to (1) determine the effect of Problem-Based Learning (PBL) on Adversity Quotient moderated by Self Efficacy, (2) determine the effect of Problem-Based Learning (PBL) on Adversity Quotient, (3) determine the effect of Self Efficacy on Adversity Quotient. This study is a quantitative study with a qualitative approach one group post-test design. The sampling technique used was cluster sampling, with a sample size of 64 students. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The validity test technique used was outer model analysis, while data analysis was carried out using Structural Equation Modeling (SEM). The results of this study are as follows. First, the implementation of PBL has a significant positive effect on students' AQ. Second, Self Efficacy is proven to moderate the effect of PBL on AQ, with students who have high Self-efficacy showing a more significant increase in AQ. Third, the implementation of PBL in science learning, especially in water pollution material, can improve students skills in facing learning challenges more effectively.